Influence of electrode spacing and gas pressure on parameters of a runaway electron beam generating during the nanosecond breakdown in SF6 and nitrogen; High Voltage; Vol. 2, iss. 2 - Tarasenko V. F. Victor Fedotovich; Zhang Cheng; Kozyrev A. V. Andrey Vladimirovich; Sorokin D. A. Dmitry Alekseevich; Hou Xingmin; Semenyuk N. S. Nataljya Stepanovna; Burachenko A. G. Aleksandr Gennadjevich; Yan Ping; Kozhevnikov V. Yu. Vasily Yurjevich; Baksht E. Kh. Evgeny Khaimovich; Lomaev M. I. Mikhail Ivanovich; Tao Shao (2017, 2017)
Title screen